2018
DOI: 10.1371/journal.pntd.0006636
|View full text |Cite
|
Sign up to set email alerts
|

The current epidemiological status of urogenital schistosomiasis among primary school pupils in Katsina State, Nigeria: An imperative for a scale up of water and sanitation initiative and mass administration of medicines with Praziquantel

Abstract: IntroductionHuman schistosomiasis, a debilitating and chronic disease, is among a set of 17 neglected tropical infectious diseases of poverty that is currently posing a threat to the wellbeing of 2 billion people in the world. The SHAWN/WASH and MAM programmes in the study area require epidemiological data to enhance their effectiveness. We therefore embarked on this cross-sectional study with the aim of investigating the prevalence, intensity and risk factors of urogenital schistosomiasis.Methodology/ Princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…After collection, parasitological examinations were performed on the same day by laboratory technicians with > 5 years of experience in urine and stool microscopy. S. haematobium eggs were detected in the urine samples via the urine centrifugation methods [13,20]. Specifically, 10 ml of urine in each tube was centrifuged at 1,500 rpm for 5 minutes at room temperature, and the sediments were transferred onto 2-4 glass slides to examine the whole pellet.…”
Section: Urine Sample Collection and Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…After collection, parasitological examinations were performed on the same day by laboratory technicians with > 5 years of experience in urine and stool microscopy. S. haematobium eggs were detected in the urine samples via the urine centrifugation methods [13,20]. Specifically, 10 ml of urine in each tube was centrifuged at 1,500 rpm for 5 minutes at room temperature, and the sediments were transferred onto 2-4 glass slides to examine the whole pellet.…”
Section: Urine Sample Collection and Examinationmentioning
confidence: 99%
“…MDA of praziquantel to at-risk populations has become the cornerstone of schistosomiasis control, especially for school-aged children (SACs), who have the high-est risk of infection [11,12]. So far, most studies on the effects of MDA were focused on reduction rates in the prevalence and intensity of disease [5,[12][13][14][15][16][17] and have not investigated as to what extent the reduction rate changes depending on the baseline value. It therefore is critical to compare changes in the prevalence and intensity of Schistosoma infection between high-and low-prevalence areas to determine the adequate frequency of MDA; however, there have been no studies in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…The former portrays Dutsin-Ma as a hypo-endemic area for urinary schistosomiasis. Previous studies recorded similar findings about the infection prevalence among School-Age Children (Bawa et al, 2016;Atalabi et al, 2018). However, the findings of Bashir et al, (2018) in Dutsin-Ma revealed a prevalence of 48.4% which falls to the meso-endemic category.…”
Section: Discussionmentioning
confidence: 54%
“…Centrifugation was carried out using Centurion Scientific Centrifuge (UK) at 400 revolution per minute for 4 minutes. Compound Binocular Microscope (x10 objective) was used to examine glass slides for the eggs of S. haematobium (Atalabi et. al., 2018).…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…After collection, parasitological examinations were carried out on the same day by laboratory technicians with more than 5 years of experience in urine and stool microscopy. S. haematobium eggs were detected in the urine samples via the urine sedimentation method, as described elsewhere [17,18]. Briefly, 10 mL of urine in each tube was centrifuged at 1,500 rpm for 5 minutes at room temperature, and the sediments were transferred onto 2-4 glass slides to examine the whole pellet.…”
Section: Urine Sample Collection and Examinationmentioning
confidence: 99%